2007
DOI: 10.1111/j.1365-2702.2005.01409.x
|View full text |Cite
|
Sign up to set email alerts
|

The fatigue experience of haemodialysis patients in Taiwan

Abstract: The results can provide a direction for interventional studies designed to reduce the patients' fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
105
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 18 publications
2
105
0
5
Order By: Relevance
“…Although biomedical explanations of fatigue prevailed, age, sleep quality, and nutrition were factors frequently mentioned by participants. There is extensive qualitative and quantitative evidence in support of the relationship between sleep quality and fatigue across chronic conditions (Kaminska et al ., 2012; Lee et al ., 2007; Menting et al ., 2016; Rongen‐van Dartel et al ., 2016; Scott, Lasch, Barsevick, & Piault‐Louis, 2011; Stuifbergen & Rogers, 1997; Wolfe, Hawley, & Wilson, 1996). In a recent study, poor sleep quality was directly associated with higher fatigue severity, and also mediated the association between lower mood and fatigue severity in RA (Rongen‐van Dartel et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although biomedical explanations of fatigue prevailed, age, sleep quality, and nutrition were factors frequently mentioned by participants. There is extensive qualitative and quantitative evidence in support of the relationship between sleep quality and fatigue across chronic conditions (Kaminska et al ., 2012; Lee et al ., 2007; Menting et al ., 2016; Rongen‐van Dartel et al ., 2016; Scott, Lasch, Barsevick, & Piault‐Louis, 2011; Stuifbergen & Rogers, 1997; Wolfe, Hawley, & Wilson, 1996). In a recent study, poor sleep quality was directly associated with higher fatigue severity, and also mediated the association between lower mood and fatigue severity in RA (Rongen‐van Dartel et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Clear overlaps in findings were also evident with regard to the description of fatigue through its impact on functioning (Magnusson et al ., 1999; Scott et al ., 2011), the distinction between tiredness caused by activity versus tiredness disproportionate to or unrelated to activity or exertion (Adamsen et al ., 2004; Glaus, Crow, & Hammond, 1996), the role of motivation in the experience of fatigue (Bennett, Goldstein, Friedlander, Hickie, & Lloyd, 2007; Hewlett et al ., 2005; Lee et al ., 2007; Mills & Young, 2008; Yngman‐Uhlin et al ., 2010), and the contribution of social comparisons to fatigue (Repping‐Wuts, Uitterhoeve, van Riel, & van Achterberg, 2008; Tack, 1990). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, these interventions can improve physical symptoms and maintain the patients' blood levels at normal degrees to relieve fatigue. 14 Univariate analysis showed that levels of fatigue differed by gender, age, marital status, employment, and the physical variables (Kt/V, URR, Hgb). However, the multivariate analysis showed that only age and duration of dialysis could predict levels of fatigue reported by HD participants.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3] Lee and colleagues have hypothesized that fatigue, considered as a combination of energy exhaustion and decreased mental activity and motivation, is associated with physiological (dialysis duration, hemoglobin, albumin, urea reduction rate, Kt/V), psychological (depression), and situational (gender, age, education, religion, employment) variables. 4 Similarly, Jhamb et al have suggested that in the dialysis population, physiological, behavioral, treatment-related, and individual characteristics may correlate with fatigue. 1 In the clinical practice, it is a common observation that anorexia is often associated with fatigue.…”
Section: Introductionmentioning
confidence: 99%